Counting stillbirth in a community - To understand the burden - Bharti Sharma; Ankit Raina; Vijay Kumar; Premananda Mohanty; Minakshi Sharma; Amit Gupta (Elsevier, 2022)
Introduction: There is huge inequality in stillbirth rates across the globe, between high and low income countries, rural and urban population. There is a large discrepancy in the reporting of stillbirth burden and estimated. This study was conducted to count the stillbirth in rural areas of two districts of Haryana, irrespective of place of delivery and to determine the geographical variations in the stillbirth occurrence. Methodology: Population based stillbirth surveillance was conducted over a period of 32 months (September 2015-April 2018). It was a part of a collaborative effort with Haryana state that comprised of strengthening of home based post natal care by the use of mobile technology in which ASHA report all pregnancies and child births to Survival of women and Children foundation. Results: During study period, 77336 deliveries were recorded from a population of 1.5 million. Total of 1327 stillbirth (>28 weeks of gestation) were identified with the stillbirth rate of 18.3 per 1000 total births. Overall institutional delivery rate was 92.8%; only 6.3% of total stillbirths delivered at home and 0.9% on the way. Conclusion: The present study provides a simple model for reporting and investigation of stillbirth irrespective of place of occurrence through the use of mobile phone. This study has shown a high stillbirth rate in spite of high institutional delivery rate. It emphasizes the need to address the reasons for delay in accessing the health care and quality of care being given rather than just by promoting institutional births.